A randomized blinded retrospective study: the combined use of micro-needling technique, low-level laser therapy and autologous non-activated platelet-rich plasma improves hair re-growth in patients with androgenic alopecia. (1st September 2020) - Gentile, Pietro; Dionisi, Laura; Pizzicannella, Jacopo; de Angelis, Barbara; de Fazio, Domenico; Garcovich, Simone
ABSTRACT: Introduction: Mini-invasive therapies based on autologous non-activated Platelet-Rich Plasma (ANA-PRP), Low-Level Laser Therapy (LLL-T), and Micro-Needling Technique (MN-T) used in combining for hair re-growth need to be standardized. Objectives: The work aims to show in vivo outcomes resulted from retrospective case-series study in which ANA-PRP + MN-T + LLL-T were used in combined in patients affected by Androgenic alopecia. Methods: 23 patients were treated, of which 13 males were classified in stage I–V by the Norwood–Hamilton scale, and 10 females were classified in stage I–III by the Ludwig scale. Assessment of hair re-growth was evaluated with photography, physician's and patient's global assessment scale, and standardized phototrichograms during a follow-up: T0 – baseline, T1 – 12 weeks, T2 – 23 weeks, T3 – 44 weeks, T4 – 58 weeks. Results: Interesting outcomes represented by a hair density increase of 81 ± 5 hairs/cm 2 and 57 ± 7 hairs/cm 2 respectively at T1 and T2 compared with baseline (173 ± 5 hairs/cm 2 at T1 and 149 ± 9 hairs/cm 2 at T2 versus 92 ± 2 hairs/cm 2 at baseline) were observed using computerized trichograms. Expert Opinion: The main limitation in the autologous regenerative therapies and biotechnologies in hair-regrowth is the extreme variability of PRP products used, in the absence of standardized protocols and widely shared. Appropriate PRP preparations have to be pick after carefully thinking about their bio-molecular specifications and intended indications for use in patients. This approach will aid in matching the optimal PRP product to specific patient factors, leading to improved outcomes and the elucidation of the cost-effectiveness of this treatment. The combined use of biotechnologies as the association of PRP with micro-needling and low-level laser therapy may improve the results in terms of hair count and hair density compared with those obtained by alone PRP. All the procedures must be performed in the full respect of international and local rules. Conclusions: The effect of the combined use of MN-T, LLL-T, and ANA-PRP has been demonstrated.